2020
DOI: 10.2147/jpr.s238458
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuropathic Pain Causes Memory Deficits and Dendrite Tree Morphology Changes in Mouse Hippocampus</p>

Abstract: Introduction: Neuropathic pain manifests in a diverse combination of sensory symptoms and disorders of higher nervous activity, such as memory deficiency, anxiety, depression, anhedonia, etc. This suggests the participation of brain structures, including the hippocampus, in the pathogenesis of neuropathic pain. The elucidation of central sensitization mechanisms underlying neuropathic pain cognitive and affective symptoms may be useful in the development of new and effective treatments for these common disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
4
19
0
3
Order By: Relevance
“…To validate our modified method, we used SNI mice-a model for neuropathic pain (Richner et al, 2011). Previous reports associate this model with altered neuronal plasticity and pain-related protein expression in the hippocampus, as well as morphological changes (Metz et al, 2009;Tyrtyshnaia and Manzhulo, 2020). Our results are consistent with that of previous reports that SNI mice exhibit a significant reduction in the number of intersections, total dendritic length, and the number of dendrites.…”
Section: Discussionsupporting
confidence: 88%
“…To validate our modified method, we used SNI mice-a model for neuropathic pain (Richner et al, 2011). Previous reports associate this model with altered neuronal plasticity and pain-related protein expression in the hippocampus, as well as morphological changes (Metz et al, 2009;Tyrtyshnaia and Manzhulo, 2020). Our results are consistent with that of previous reports that SNI mice exhibit a significant reduction in the number of intersections, total dendritic length, and the number of dendrites.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to dendritic spine dysgenesis in the spinal cord, neuropathic pain produces spine changes in higher brain regions, including the hippocampus. Similar to the structural changes in the spinal cord, neuropathic pain after chronic constriction injury induced alterations in dendritic tree morphology as well as altering the type and number of dendritic spines in the mouse hippocampus (Tsai et al, 2009;Tyrtyshnaia and Manzhulo, 2020). This finding suggests that neuropathic pain produces aberrant structural plasticity in diverse neuronal structures involved in the processing of sensory information (Tsai et al, 2009).…”
Section: Dendritic Spines In Higher Brain Regionsmentioning
confidence: 79%
“…This finding suggests that neuropathic pain produces aberrant structural plasticity in diverse neuronal structures involved in the processing of sensory information (Tsai et al, 2009). The dysregulation of spines in the hippocampus might explain the connection between chronic neuropathic pain and the development of anxiety and depression, which are often comorbid in patients with neuropathic pain (Woo, 2010;Golden et al, 2013;Lee et al, 2018;Tyrtyshnaia and Manzhulo, 2020). Acute increases in dendritic spine turnover of primary cortical somatosensory circuits accompany neuropathic pain after peripheral nerve injury (S. K. Kim et al, 2016).…”
Section: Dendritic Spines In Higher Brain Regionsmentioning
confidence: 99%
“…Interestingly, a study reported that the generation of new neurons in the amygdala was promoted during neuropathic pain [129]. The hippocampus displayed changes in dendritic spine morphology and neurogenesis rates following nerve injury [130,131]. These alterations are related to several molecules, such as tumor necrosis factor-alpha [132] and glycogen synthase kinase-3 beta [133].…”
Section: Discussionmentioning
confidence: 99%